The study of computed tomography angiography in the evaluation of acute stroke - Nayak, Rakesh C.; Gehlot, Kushal B.; Rahlot, Tarun K.; Kardam, Narendra R.; Choudhary, Mayank; Naik, Pratik N. (International Journal of Research in Medical Sciences, 2024)
Background: When it comes to residual lumen diameters and areas, calcifications, and stenose length, computed tomography angiography (CTA) offers genuinely anatomic, non-flow dependent information. Compared to traditional catheter arteriography, CTA is less costly, causes less discomfort to patients, and has a significantly lower risk of stroke and other vascular complications. Additionally, it is helpful when performing magnetic resonance (MR) is not recommended or is not possible. Generally speaking, CTA is more accessible than MR, particularly in emergency situations. As there are no limitations on the kind and quantity of related support equipment, such as intravenous pumps, ventilators, or monitoring hardware, CTA, in contrast to MR angiography (MRA), is well suited for the imaging of critically ill patients. Our goal was to assess how useful CT angiography is for determining the etiology of vessel occlusion and stroke. Methods: Non enhancing CT scan of all patients was evaluated first for significant findings, after that contrast enhanced scan was evaluated and compared with non-enhancing CT scan. Direct volume rendering (dVR) is the most sophisticated method for 3D visualization. When dVR is used to create CT angiograms, the voxels of high attenuation containing information about bony structures are selected separately from those voxels with an attenuation between 100 and 300 HU containing information about contrast- enhanced vascular structures. Results: We observed sensitivity of CTA in evaluation of acute stroke as 93.33%, specificity 80%, positive predictive value (PPV) 87.5% and negative predictive value (NPV) 88.88%. Conclusions: CT angiography, when closely correlated with patients’ clinical conditions, has the potential to become the screening method of choice for evaluating patients with significant vascular lesions amenable to acute intracranial transcatheter thrombolytic therapy.